Paranoia and Christianity in Maurice Dantec’s Crime Fiction - Jean-Louis Hippolyte (Studies in 20th & 21st Century Literature, 2009)
Maurice Dantec is “a prophet, a mystic, a Christian soldier, Zionist and pro-American, anti-secular and militantly counter-revolutionary. In short, the last scandal of French literature,” according to his editor David Kersan. Dantec’s brand of punk neo-Christian literary activism may feel somehow out of place in a literary milieu still beholden to the existentialism of Sartre and the revolutionary ethos of the 1960s. But Dantec’s “disgust” (of Old Europe, the creeping menace of Islam and the rampant march of secularization) bears witness to a larger malaise. Along with Michel Houellebecq and Peter Sloterdijk, he testifies to the opening of a new chapter in the culture wars, to the rise of a new group of “écrivains maudits” who have decided to vehemently question postmodern nihilism and economic globalization. Finally, Dantec’s fiction makes a case for the need for faith in a Godless world. This essay is concerned with Dantec’s paranoid politics as they appear in his fiction, and most notably in his latest Christian futuristic trilogy. It is also concerned with the relevance of conservative Christian dogma in his work, both formally and rhetorically.
Keywords: David Kersan; Maurice Dantec; Zionist; pro-American; Christian; Christianity; Michel Houellebecq; Peter Sloterdijk; culture wars; écrivains maudits; postmodern nihilism; economic globalization; Christian dogma